Information rights as a civil-legal category - Тихомиров, Олександр Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In this article the author reviews information rights as a civil-legal category in the context of the human rights generation division and of the role and understanding of information in modern society transformation. It is mentioned in the article that according to the deep informatization of modern life and general recognition of information society priorities, information rights are important not only as a certain set of powers, but also as a priority vital interest, implementation of which has an influence on the modern person’s activity. Not that information as some data should be considered as an object of information rights, but more information as knowledge, that determines also the ways of protection of such rights. Although the problem of information rights was brought to the legal reality by new challenges of human civilization, their legal nature doesn’t actually contain anything new – that is more the result of detailing of fundamental human rights as a tribute to today’s realities. The author emphasizes that as legal regulation, including theoretical, is characterized by certain backwardness of real life’s needs, in the future it can be predicted that, with the realization of need to improve civil legal mechanisms of human rights’ protection, civil legislature will be filled with a new provisions regarding peculiarities of human rights in an information field, or in other words information rights.